Pobočni procesi in človek - Komac, Blaž (Geografija Slovenije, 2007)
The book brings a thorough review of slope processes, their causes and consequences. Both, prehistoric and recent slope processes in Slovenia are described into deatil. Authors investigated the main characteristics of slope processes according to the type of movement (flow, slide, fall), their extent and effects. As geographers, they are interested mainly in the links between natural processes and man. More than sixty different slope processes in Slovenia are described into detail, based upon field work and examination of numerous sources. In this way all types of slope processes are included and described.Review of circumstances if followed by a discussion about the importance of slope processes for spatial planning as well as methodological and practical instructions for hazarad maps elaboration with different methods. Two deterministic methods and a one probabilistic are presented.The documentary value of the book is also increased by the fact that it brings a chapter about a memory of inhabitants on slope processes, as it has been preserved in sacred literature and aitiological narratives.The book can be used for thorough studies of physical geography and related sciences. Plentiful documentary material makes it useful for everyone who would like to explore nature in Slovenia.